Sources of perceided social support and depression among primary school adolescents in Kelantan and cross-cultural adaptation of its instrument - Rani, Nor Azila (2021)
Background: Adolescent depression is a serious health concern nowadays, and perceived social support influences the outcome. While several validated adult social support measures exist, few validated child and adolescent measures are available. Currently, no Malay measures of comprehensive social support for children and adolescents are available in Malaysia. Moreover, most adolescent depression research was conducted among secondary school students, and less focused on primary schools, thus putting them at risk of going undiagnosed and untreated. Therefore, this study considers the role of multiple sources of perceived social support in primary school adolescent depression. Objectives: This study aims to translate, cross-culturally adapt, and validate the Child and Adolescent Social Support Scale (CASSS) for Malay-language-speaking schoolaged adolescents; to assess the level of perceived social support from different sources; to determine the prevalence of depression among primary school adolescents in Kelantan and to further determine the association between sources of social support and socio-demographic factors with depression among primary school adolescents in Kelantan. Methods: This study was conducted in two phases. The first phase was a cross-cultural adaptation of the CASSS to fulfill the first objective. The CASSS contains 60 items that assess the frequency and importance of perceived social support from parents, teachers, classmates, close friends, and other people in school. Only the 6-Likert scale frequency rating was used in this study. The CASSS underwent translation and validation processes following an established guideline. Six expert panels validated the content, while ten students were chosen for face validation. The Malay version was next validated among 382 school-going adolescents aged 10 to 16 in Kota Bharu. Confirmatory factor analysis (CFA) using robust maximum likelihood estimation method was utilised to examine the internal structure construct. The second, third and fourth study's objectives were fulfilled in the second phase using a cross-sectional study design. From August 2020 to September 2020, 576 students aged 10 and 11 years old from six randomly chosen government primary schools in three randomly selected districts in Kelantan were recruited. The self-administered Malay-validated version of CASSS (M-CASSS) and the Malay Children's Depression Inventory (MCDI) were used to collect data. Data were analysed using simple and multiple logistic regression for the second phase. Results: The M-CASSS retained the original five-factor construct with 60 items. Its content and face validity showed excellent results, with S-CVI/Ave=0.94 and SFVI/ Ave=0.99, respectively. Following several justified suggestions for misfits during the analysis, five different structure models were examined in the CFA. The selected final model suggested the existence of five factors, with four correlated items within factors (O1 ~~ O2, O10 ~~ O11, T3 ~~ T4, and T10 ~~ T12). The final model showed acceptable fit indices (χ2/df = 1.58, SRMR=0.05, RMSEA=0.04, CFI and TLI close to 0.90, AIC= 75841, BIC= 76370). Factor loadings ranged between 0.419 and 0.764, and Raykov's reliability was 0.961. All factors were distinct, with factor correlations being < 0.85. In phase two, this study discovered that students regarded their teachers as the most supportive. About 131 (22.7%) of them were screened as depressed. Only parents' support significantly protected them from depression, not the other four